The transcriptional factor TtsI is involved in a negative regulation of swimming motility in Mesorhizobium loti MAFF303099 - Duarte, Cecilia Magalí (2016)
Mesorhizobium loti MAFF303099 has a functional Type III secretion system (T3SS) that is involved in the determination of competitiveness for legume nodulation. Here we demonstrate that the transcriptional factor TtsI, which positively regulates T3SS genes expression, is involved in a negative regulation of M. loti swimming motility in soft-agar. Conditions that induce T3SS expression affect flagella production. The same conditions also affect promoter activity of M. loti visN gene, a homolog to the positive regulator of flagellar genes that has been described in other rhizobia. Defects in T3SS complex assembly at membranes limited the negative regulation of motility by the expression of TtsI.